Perancangan Aplikasi Sistem Informasi Akuntansi Persediaan Barang Menggunakan Microsoft Access 2016 (Studi Kasus Toko Villi Bandung) - Suvilia Giovani; Ira Novianty (Indonesian Accounting Literacy Journal, 2020)
Toko Villi is a trading business unit engaged in the food sector with snacks as their main product. The Villi shop sells snacks with dozens of types, and each type has a very large number from tens to hundreds of units. However, in its business activities, Toko Villi does not keep records of the goods they have. The Villi shop does not perform data processing and only relies on documents such as sales and purchase invoices as the basis for the entry and exit of goods. Based on the problems faced by these companies, the authors designed an inventory accounting information system application that will assist the company in running its business. This research is a qualitative research with a case study and development approach. The data analysis tool used in designing this application is the waterfall model SDLC (Software Development Life Cycle). This inventory application is designed using Microsoft Access 2016 and is tailored to the needs and desires of the company. This design is expected to meet the company's needs for information such as stock of goods, transaction reports of incoming and outgoing goods and reports of out of stock goods.